Comparison of the effects of exergaming and balance training on dynamic postural stability during jump-landing in recreational athletes with chronic ankle instability. - Sadaf Sepasgozar Sarkhosh; Roya Khanmohammadi; Zeinab Shiravi (PLoS ONE)
The primary inquiry of this study was to determine if exergaming is more effective than balance training in improving dynamic postural control during jump-landing movements among athletes with chronic ankle instability (CAI). Additionally, the study aimed to compare the effectiveness of these interventions on clinical and psychological outcomes. This study was a randomized, single-blinded, controlled trial in which participants were assigned to either an exergaming group or a balance training group. Outcome measures were assessed before, after, and one month following the intervention. Primary outcomes included the stability index (SI) and time to stabilization (TTS) in the anteroposterior (AP), mediolateral (ML), and vertical (V) directions, the dynamic postural stability index (DPSI), and the resultant vector time to stabilization (RVTTS). Secondary outcomes included performance, fear of movement, and perceived ankle instability, measured using the side-hop test, the Tampa Scale for Kinesiophobia (TSK), and the Cumberland Ankle Instability Tool (CAIT), respectively. Results indicated a significant decrease in ML SI in both groups one month after treatment compared to before and after treatment (P = 0.013 and P<0.001, respectively). Additionally, one-way ANCOVA revealed a significant difference between the groups post-treatment (F(1,31) = 6.011, P = 0.020, η2 = 0.162) and one month post-treatment (F(1,31) = 4.889, P = 0.035, η2 = 0.136), with ML SI being significantly lower in the exergaming group than the balance training group at both time points. In both group, the DPSI also decreased significantly one month post-treatment compared to before and after treatment (P = 0.040 and P = 0.018, respectively). Both groups showed improvements in performance, severity of perceived ankle instability, and fear of movement. Thus, the study concluded that both exergaming and balance training effectively improved postural control during jump-landing, with exergaming showing superior performance in the ML direction both after and one month post-treatment. In terms of clinical and psychological outcomes, both interventions were effective, with neither showing superiority over the other.